Slovar krajšav - Kompara Lukančič, Mojca (University of Maribor Press, 2025)
Dictionary of Abbreviations. The monograph, entitled Dictionary of Abbreviations, is the first work of its kind in Slovenia. It is a work that provides readers with a one-stop glossary of foreign abbreviations, their derivations, their translated equivalents in the Slovenian language and, if the latter exist, also Slovenian abbreviation equivalents. The dictionary includes foreign abbreviations used in the Slovenian context, the set of which was compiled with the help of an algorithm for automatic recognition of abbreviations in electronic texts, also after several years of manual collection. As can be seen from the example above, the dictionary includes a set of abbreviations from foreign languages, namely 10 foreign languages. The most representative foreign abbreviations come from English, French, Latin, Italian and German, but the dictionary also includes abbreviations in other languages, but fewer in number, e.g. Croatian, Spanish, etc. As can be seen from the example above, each source language is indicated by an abbreviation, e.g. Latin, followed by the expansion and any other spellings of the abbreviation, followed by the Slovene translation equivalent and, if it exists, the Slovene equivalent of the abbreviation.